(untitled) (Tempo e Argumento, 2020)
In the early years of the 21st century, we can see the strength of the feminist movement and political demands committed on establishing the role of women in public sphere. In the same context, there is also an increased interest in comics as a language endowed with very specific procedures, where the visual narrative makes it possible to represent other perspectives on human experience in time. It is not by chance that comics allow visibility and represents in a unique way the feminist struggles of the time, which is expressed, in turn, in a growing academic production that seeks to review the place of women in the comics art world. This article is an approximation to this vast bibliographic corpus, focusing the analysis on some important works dedicated to investigate the place of women in comics, including an analysis on recent Brazilian comics scholarship. The conclusion points to some of the possibilities for future research, highlighting the specificities of the language of comics to narrate and graphically represent the female condition in the contemporary world. Keywords: Comics. Women History. Feminism.